2021
DOI: 10.1002/ab.21978
|View full text |Cite
|
Sign up to set email alerts
|

Pornography, impersonal sex, and sexual aggression: A test of the confluence model in a national probability sample of men in the U.S.

Abstract: This paper reports findings on men's exposure to extreme pornography, impersonal sexuality, and sexual aggression from the National Survey of Porn Use, Relationships, and Sexual Socialization, a U.S. population-based probability study. Despite Malamuth's confluence model (CM) of sexual aggression positing that an impersonal approach to sex interacts with exposure to pornography to predict the likelihood of committing sexual assault, only a few studies have actually tested this prediction.Additionally, the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Although a few national studies of perpetration have been conducted, they do not contribute to the prevalence database. For example, a recent report of a representative national sample of adult men examined the relationship of pornography, impersonal sex, and sexual aggression (Wright et al, 2021). However, the study defined sexual aggression as verbal pressure for sex, and measured this construct by one yes/no question.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few national studies of perpetration have been conducted, they do not contribute to the prevalence database. For example, a recent report of a representative national sample of adult men examined the relationship of pornography, impersonal sex, and sexual aggression (Wright et al, 2021). However, the study defined sexual aggression as verbal pressure for sex, and measured this construct by one yes/no question.…”
Section: Introductionmentioning
confidence: 99%
“…Since this time, further research has been conducted that is less supportive of the theorized synergistic three-way interaction between HM, IS, and pornography use that lies at the heart of Confluence Model accounts of the relationship of pornography use and sexual aggression. For example, a recent nationally representative survey of American males sought but failed to find a positive two-way synergistic interaction between IS and pornography use when predicting sexual aggression (Wright et al, 2021). Some may argue that this study did not properly test Confluence Model theorizing because it did not consider the three-way interaction between HM, IS, and pornography use.…”
Section: Pornography Use In the Confluence Modelmentioning
confidence: 86%
“…For instance, the Confluence Model (Malamuth, et al, 2000) posits that pornography use, hostile masculinity, and sexual promiscuity work together to influence sexually aggressive behavior. Research has found support for this theory (Huntington et al, 2022; Malamuth et al, 1995, 1996; Wright et al, 2021), specifically when examining the interaction between pornography use, impersonal sex, and sexual coercion. For instance, recently Wright et al (2021) found that individuals who were exposed to violent pornography and impersonal in their approach to sex were more likely to engage in sexual coercion than individuals who were impersonal in their approach to sex and not exposed to violent pornography.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has found support for this theory (Huntington et al, 2022; Malamuth et al, 1995, 1996; Wright et al, 2021), specifically when examining the interaction between pornography use, impersonal sex, and sexual coercion. For instance, recently Wright et al (2021) found that individuals who were exposed to violent pornography and impersonal in their approach to sex were more likely to engage in sexual coercion than individuals who were impersonal in their approach to sex and not exposed to violent pornography. Similarly, Huntington et al (2022) found that impersonal sexual orientation and violent pornography exposure were related to non-contact sexual coercion, while hostile masculinity and violent pornography exposure were related to sexual coercion involving contact.…”
Section: Literature Reviewmentioning
confidence: 99%